Platelet-activating factor enhancement of calcium influx and interleukin-6 expression, but not production, in human microglia - Prasongchai Sattayaprasert (2018)
Calcium-sensitive fluorescence microscopy and molecular biology analysis have been used to study the effects of platelet-activating factor (PAF) on Intracellular calcium [Ca2+]1 and IL-6 expression in human microglia. PAF (applied acutely at 100 nM) elicited a biphasic response In [Ca2+]1 consisting of an initial rapid increase of [Ca2+]1 due to release from internal stores, followed by a sustained influx. The latter phase of the [Ca2+]1 increase was blocked by SKF96365, a non-selective store-operated channel (SOC) inhibitor. RT-PCR analysis showed PAF treatment of microglia induced expression of the pro-inflammatory cytokine IL-6 in a time-dependent manner which was blocked in the presence of SKF96365. However, ELISA assay showed no production of IL-6 was elicited at any time point (1-24 h) for microglial exposures to PAF, These findings suggest that PAF stimulation of human microglia induces expression, but not production, of IL-6 and that SOC-mediated [Ca2+]1 influx contributes to the enhanced expression of the cytokine. © 2005 Sattayaprasert et al; licensee BioMed Central Ltd.